Toward a Holistic Framework of Islamic Business Ethics: Insights from Leadership, Halal Practices, and Finance in a Digital Age - Rangkuti, Muhammad Yusuf (Yayasan Sinergi Kawula Muda, 2023)
In an increasingly interconnected global economy, ethical considerations have become central to sustainable business practices. This narrative review examines business ethics from an Islamic perspective by analyzing three main domains: ethical leadership, halal industry operations, and Islamic financial institutions. Using a thematic analysis of recent peer-reviewed literature, the study identifies core principles—such as justice, transparency, stakeholder engagement, and Shariah compliance—as pivotal to Islamic business ethics. The review reveals that leadership modeled on the Prophet Muhammad’s values fosters ethical organizational cultures and enhances employee trust and commitment. Additionally, the halal industry demonstrates substantial regional variation in ethical practices, with Malaysia and Indonesia offering more structured frameworks compared to the Middle East. In Islamic finance, Shariah-based governance, consumer trust, and social responsibility initiatives emerge as key differentiators from conventional banking. Despite these strengths, challenges remain in the form of fragmented regulatory systems, ethical inconsistencies, and cultural resistance. The study recommends institutional reforms, enhanced educational frameworks, and inclusive stakeholder engagement as strategic responses. These findings highlight the need for integrated approaches that align religious ethics with contemporary business challenges. This review contributes to the academic discourse by offering practical insights and policy-oriented recommendations to support the ethical development of Islamic business ecosystems.